Analisisa Usaha Produksi Rumput Laut di Desa Jumiang Timur Kecamatan Pademawu Kabupaten Pamekasan - Mohammad Taufiq Hidayat (Yayasan Literasi Sains Indonesia, 2022)
Optimizing efforts to increase food security requires innovation in increasing the effectiveness of commodity flows through better coordination. One of the Indonesian commodities that has great potential but has so far received little attention is Seaweed, which is one of the most widely produced and consumed plant commodities in Indonesia. Seaweed cultivation is carried out by the community in East Jumiang Village because this area is very suitable for growing seaweed plants, so seaweed farming is one of the existing farmer activities, besides that the community is more knowledgeable about traditional seaweed cultivation methods. In East Jumiang Village, farmers Cultivate seaweed using random method. This study aims to determine the efficiency of seaweed farming in Jumiang East Village, Pademawu District, Pamekasan Regency. The analysis used in this study using Revenue Cost Ratio (R/C) is cost efficiency. The results of the research on the efficiency of seaweed cultivation in Jumiang East Village, Pademawu District, Pamekasan Regency are: fixed costs in seaweed farming are Rp. 1575000 and variable costs are Rp. 316000 so the total cost of seaweed farming is Rp. 1891000, revenue is Rp. 540000 and profit is Rp. 1351000. The value of R/C Ratio > 1, which is 2.50, means that seaweed production farming in Jumiang Timur Village, Pademawu District, Pamekasan Regency, efficient and profitable because with a capital of 2.00 you will get a profit of Rp. 2.50.